Study on risk factors of respiratory distress syndrome in term neonates: a retrospective case-control study - B., Sunil; Nithya, E.; N., Girish (International Journal of Contemporary Pediatrics, 2019)
Background: Respiratory distress syndrome (RDS) is one of the most common causes of neonatal respiratory failure and neonatal death. It is more common in preterm neonates but also been found in term and late preterm neonates. This study aims at studying the risk factors for developing RDS in term neonates. Objectives was to study the maternal and perinatal risk factors for RDS in term neonates. Methods: This is a retrospective case control study conducted in neonatal intensive care unit of tertiary care centre. A total of 100 term neonates with RDS were taken as cases and 150 normal term neonates were taken as control. Data were collected from the hospital NICU records, maternal and neonatal history was taken. The χ2 tests or Fisher’s exact text were used for one-way risk factor analysis. The effects of multiple factors on term neonatal RDS were analyzed using logistic regression analysis. Results: In our study RDS in term neonates was significantly associated with following risk factors like selective cesarean section, male sex, SGA, oligohydramnios, MSAF, severe fetal distress, birth asphyxia, PROM, and maternal-fetal infection. Among the significant risk factors severe birth asphyxia, maternal-fetal infection, PROM, MSAF were showing positive association with RDS in full-term neonates. Conclusions: Several high-risk factors such as severe birth asphyxia, maternal-fetal infection, PROM, and MSAF were closely correlated with full-term neonatal RDS. Hence these could provide a significant reference for the diagnosis and treatment of term neonatal RDS.